Environmental justice dialogues and the struggle for human dignity in the deciduous forest of Bangladesh - Ahmed, Farid, author; Low, Nicholas P., author (Colorado State University. Libraries, 2017)
The paper presents environmental justice dialogues in the Madhupur Garo community in Bangladesh. The Garo community, which identifies itself as adivasi meaning 'indigenous', has occupied the deciduous forest of Madhupur in Bangladesh for centuries, developing a symbiotic relationship with nature. An environmental justice movement, called the "Eco-park Movement" has long been protesting a government development plan to establishing an "eco-park'' in the Madhupur deciduous forest. The eco-park plan has interfered with the Garo's right to life and livelihood as well as threatening them with possible eviction from their traditional land. From their protest movement, the concept of environmental justice has acquired a meaning with emphasis on human dignity. The Garo community not only defines environmental injustice as a lack of access to the decision-making process, information and judiciary but includes other elements: obstruction to fair access to environmental resources for livelihood, threat to the economy, health, trade, education, security, privacy and right to life. Finally, the Garo connect all these environmental human rights issues with rights to self-determination and human dignity.
Presented at the Environmental justice in the Anthropocene symposium held on April 24-25, 2017 at the Lory Student Center, Colorado State University, Fort Collins Colorado. This symposium aims to bring together academics (faculty and graduate students), independent researchers, community and movement activists, and regulatory and policy practitioners from across disciplines, research areas, perspectives, and different countries. Our overarching goal is to build on several decades of EJ research and practice to address the seemingly intractable environmental and ecological problems of this unfolding era. How can we explore EJ amongst humans and between nature and humans, within and across generations, in an age when humans dominate the landscape? How can we better understand collective human dominance without obscuring continuing power differentials and inequities within and between human societies? What institutional and governance innovations can we adopt to address existing challenges and to promote just transitions and futures?
Keywords: sustainable development; environmental justice; capabilities and conflicts; human dignity; Eco-Park Movement; right to life; Madhupur